2001
DOI: 10.1039/b008050k
|View full text |Cite
|
Sign up to set email alerts
|

Paper surface modification by plasma deposition of double layers of organic silicon compounds

Abstract: In this work, filter paper was coated with plasma depositions of hexamethyldisilazane (HMDS), and double layers of HMDS and n-hexane, and HMDS and tetraethyl orthosilicate (TEOS). In the case of double layers of HMDS and TEOS, TEOS deposition times of 2, 4 and 6 minutes were studied. The double layers were interfaced by an intermixing layer, in which both reagents were present. All coating films formed adhered well to the substrate, and resulted in water repellent paper surfaces with apparent water contact ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 10 publications
3
22
0
1
Order By: Relevance
“…In contrast, carbon tetrafluoride plasma gave a high surface fluoride content and a very hydrophobic surface was created. There are also several other studies in which low-pressure plasma with fluorocarbon or silicon compounds has rendered the paper highly hydrophobic [4,5,[10][11][12]. Denes et al also found that low-pressure cold plasma treatment increased the surface roughness of surfacesized security papers.…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, carbon tetrafluoride plasma gave a high surface fluoride content and a very hydrophobic surface was created. There are also several other studies in which low-pressure plasma with fluorocarbon or silicon compounds has rendered the paper highly hydrophobic [4,5,[10][11][12]. Denes et al also found that low-pressure cold plasma treatment increased the surface roughness of surfacesized security papers.…”
Section: Introductionmentioning
confidence: 98%
“…One of their great advantages is the ease of manipulation, since they are liquids of low toxicity. For example, Tan et al reported the creation of hydrophobic filter papers with the water contact angle of 120°by modifying the surface of HMDS coating [6].…”
Section: Introductionmentioning
confidence: 99%
“…Most of them present conformal deposition on microchannels and others can be used as selective membranes (2-propanol and acetaldehyde plasma polymerized films). The production of these films makes use of new plasma deposition procedures, mainly closed chamber mode, intermixing and double layer deposition [26][27][28]. "Closed chamber mode means that there is no flow of reagent during the plasma deposition.…”
Section: Introductionmentioning
confidence: 99%